PROBLEMATIKA BAYI TABUNG - Syamsuddin Sakka (IAIN Palopo, 2020)
As technology gets more advanced the more Islamic law is in need to regulate it. The use of technology must be in accordance with the provisions of Sharia, or at least not contrary to it, as such in the issue of In Vitro Fertilization (IVF) and related matters. Furthermore, technological advances are used by people to facilitate and help them live dignified lives. This research concludes that the use of technology, especially in the field of health, must pay attention to religious rules, morals, manners in general, and should not degenerate human dignity. The utilization of IVF technology is required only by people who are scientifically and religiously trusted. In its implementation and development, it needs to be closely monitored by the government, religious organizations, especially the Indonesian Ulema Council (MUI), academicians, and the general public. There are several problems arising from IVF, such as first, an IVF after a divorce, which in this case Islamic Scholars agreed to state the process as haram (forbidden). Second, freezing embryo, sperm, or ovum, in this case, some Islamic Scholars permit it under the condition that there is a real benefit that can be derived from it and it should be devoid from any misuse. Third, related to the act of destroying the remaining embryo, in this case, it must be tried so that there is no remaining embryo in the process. Even if there is, it can be stored or left to die naturally.